2017
DOI: 10.1002/joc.5183
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of non‐stationarity in a local climatology of rainfall extremes in northern Italy

Abstract: ABSTRACT:The stationarity of rainfall annual maxima statistics is investigated in a northern Italian area characterized by important spatial variations in orography and precipitation climatology. Climatic changes in Italian recorded temperature series are widely acknowledged. In 2016, though, there is still discussion on the stationarity of the statistics of precipitation and its extremes in Italy. By means of standard hypothesis testing techniques, it is shown, for the first time in Italy, that changes in rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…Conflicting outcomes then arise from these past studies. More specifically, Crisci et al (), Arnone et al (), Saidi et al (), and Uboldi and Lussana () have found general increasing trends for short‐duration rainfall, respectively, in Tuscany, Sicily, Piedmont, and Lombardy regions, while Caloiero et al () have found decreasing trends in Calabria. Finally, Cifrodelli et al () and Gallus et al () have found that trends are not significant in Umbria and Liguria regions, respectively.…”
Section: Introductionmentioning
confidence: 97%
“…Conflicting outcomes then arise from these past studies. More specifically, Crisci et al (), Arnone et al (), Saidi et al (), and Uboldi and Lussana () have found general increasing trends for short‐duration rainfall, respectively, in Tuscany, Sicily, Piedmont, and Lombardy regions, while Caloiero et al () have found decreasing trends in Calabria. Finally, Cifrodelli et al () and Gallus et al () have found that trends are not significant in Umbria and Liguria regions, respectively.…”
Section: Introductionmentioning
confidence: 97%
“…Studies on extremes are still rare and have focused on relatively short periods and/or on small study areas (often limited by political borders). For example, Scherrer et al () found significant increases in daily extreme precipitation indices at several stations in the southern Alpine sector of Switzerland over 1901–2014, while Uboldi and Lussana () found a significant increase in daily and sub‐daily extreme precipitation in a small area in northeastern Lombardy over the second half of the 20th century. No study exists for the southern Alps as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…However, the signal of extreme precipitation change with temperature has been clearly detected, and the precipitation extreme is expected to increase by 7% per degree warming according to the Clausius-Clapeyron (CC) relation which states that the atmosphere can hold about 6%-7% more water vapor per degree of warming before saturation occurs (Dhakal et al 2015;Gu et al 2017;Jakob et al 2011;Kharin et al 2007; She et al 2015;Uboldi and Lussana 2017). Extreme precipitation is expected to increase by 7% at daily time scales and 14% at subdaily time scales with 18C increase in temperature in China (Wang et al 2018).…”
Section: Variations In Annual Precipitation Over Chinamentioning
confidence: 99%
“…Some researchers believe that compared to climatic mechanisms, endogenous catchment mechanisms (e.g., groundwater table, baseflow, and vegetation) govern nonstationarity in rainfall-runoff relationships (Deb et al 2019). Many studies have reported that nonstationarity of extreme precipitation and peak flow at subdaily and daily time scales (Dhakal et al 2015;Gu et al 2017;Jakob et al 2011;Kharin et al 2007;Lewis 2018;Prosdocimi et al 2014;Seth and Sisson 2011;She et al 2015;Uboldi and Lussana 2017). Extreme precipitation is expected to increase by 7% per degree of temperature at daily time scales and it exhibits a higher increasing rate at subdaily time scales (Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%